Diagnostic test of Brief Peripheral Neuropathy Screen as Distal Sensory Polyneuropathy-HIV Diagnostic Tool - Joko Rudyono1, Mudjiani Basuki1, Erwin Astha Triyono2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Distal sensory polyneuropathy (DSP) is the most common human immunodeficiency virus (HIV)-associated peripheral neuropathy with a prevalence of 30-67%. Brief peripheral neuropathy screen (BPNS) examination is a non-invasive, fast, cheap, easy-to-do diagnostic method, and one of the clinical tools that can be used to diagnose HIV-DSP. This study to assess the BPNS diagnostic test as a DSP diagnostic tool in HIV patients. The cross-sectional study was conducted on HIV patients that allegedly having DSP. All subjects were examined by BPNS and nerve conduction study (NCS), then the results were analyzed by chi-square test of a 2x2 Table. There were 42 subjects enrolled in this study. The mean patients were 38.88±8.62 years and most of the male patients were 24 subjects (57.14%). Most of the patients had high school education by 20 (47.61%) subjects and did not take anti-retroviral (ARV) by 18 (42.85%) subjects. Most of the research subjects conducted BPNS disturbed examination by 27 (64.28%) subjects and examination of NCS obtained positive DSP by 30 (71.4%) subjects. The obtained sensitivity of 83% BPNS, 83% specificity, 93% positive predictive value, the negative predictive value of 67%, a positive likelihood ratio of 5.00, and a negative likelihood ratio of 0.20. BPNS examination with 83% sensitivity and 83% specificity can be used as a DSP diagnostic tool in HIV patients.